XFEM Simulation of Pore-Induced Fracture of a Heterogeneous Concrete Beam in Three-Point Bending - Zhang, C.C.; Yang, X.H.; Gao, H. (Проблемы прочности, 2018)
The extended finite element method with the linear softening law is employed to simulate poreinduced crack initiation and propagation in heterogeneous plain concrete beams in three-point bending. A series of numerical simulations was performed and experimentally validated. The crack was found to always initiate at the beam bottom in the point nearest to the pore, propagating through it. When the pore has a larger offset from the beam midspan, the beam displays higher fracture resistance and energy dissipation spent for fracture. With an increase in a distance from the beam bottom, the ultimate load also increases, but the energy dissipation slightly varies. The pore sizes have a little effect on the fracture resistance of the concrete beam. Моделирование вызванных пористостью зарождения и распространения трещины в бетонных балках неоднородной структуры при трехточечном изгибе выполнено с помощью расширенного метода конечных элементов и закона линейного разупрочнения. Проведен ряд операций численного моделирования, проверенных экспериментально. Установлено, что трещина всегда зарождается на нижней грани балки в точке, ближайшей к поре, прорастая сквозь нее. Если пора в большей степени смещена относительно среднего пролета балки, последняя проявляет более высокое сопротивление разрушению и диссипацию энергии, затрачиваемой на разрушение. По мере увеличения расстояния от поры до нижней грани балки допустимая нагрузка также возрастает, а диссипация энергии несколько изменяется. Показано, что размеры пор оказывают незначительное влияние на сопротивление бетонной балки разрушению.